Pengaruh Collateral Assets, Kebijakan Hutang, dan Investment Opportunity Terhadap Kebijakan Dividen - Angga Firmansyah Putra; Syaiful Bahri (Owner : Riset dan Jurnal Akuntansi, 2023)
The purpose of study is to examine the effect of collateral assets, debt policy, and investment opportunity on dividend policy. The type of research is quantitative approach. The research population food and beverage companies listed on the Indonesia Stock Exchange in 2019-2021. The sample of research by using purposive sampling of the research sample selection of 11 food and beverage companies. The data analysis technique used classical assumption test, descriptive analysis, multiple linear regression, hypothesis testing and determination test. The results show that collateral assets, debt policy, and investment opportunity have no effect on dividend policy. Recommendations for further research are to expand the object and period of the research year so that the research results are more accurate and can be used as a general reference.